Penurunan Susut Jaringan Dengan Penertiban Pemakaian Tenaga Listrik - Novi Gusti Pahiyanti (Sekolah Tinggi Teknik - PLN, 2019)
The decrease in the shrinkage of the distribution network can be done through controlling the use of electricity. Before the use of electricity by consumers, electricity in the distribution network is then fed to the APP (meter and gauge) of the customer's meter and can then be used by customers for daily use. Operational control of electric power expansion that is in the PLN is an activity carried out by the PLN so that there is no loss or can minimize the losses experienced. The truth of measuring meter energy in APP has several obstacles, such as the wrong reading of kwh meters, theft of electricity, use of electricity without measuring the meter, wiring and others. Basically the shrinkage itself is divided into the first two technical losses and non-technical losses in PT PLN (Persero) Teluk Naga Area, in non-technical shrinkage is a problem that is very vigilant because of this shrinkage PLN gets a lot of losses from customers such as affecting power limit, affecting energy measurements can reach 8257.9 kWh / month from 16 customers and experiencing losses of 13809.8 kWh / month therefore customers who make these deviations will be subject to sanctions in the form of a fine of Rp.332,830,661 for all customers who do deviation. The decrease in the shrinkage of the distribution network can be done through controlling the use of electricity. Before the use of electricity by consumers, electricity in the distribution network is then fed to the APP (meter and gauge) of the customer's meter and can then be used by customers for daily use. Operational control of electric power expansion that is in the PLN is an activity carried out by the PLN so that there is no loss or can minimize the losses experienced. The truth of measuring meter energy in APP has several obstacles, such as the wrong reading of kwh meters, theft of electricity, use of electricity without measuring the meter, wiring and others. Basically the shrinkage itself is divided into the first two technical losses and non-technical losses in PT PLN (Persero) Teluk Naga Area, in non-technical shrinkage is a problem that is very vigilant because of this shrinkage PLN gets a lot of losses from customers such as affecting power limit, affecting energy measurements can reach 8257.9 kWh / month from 16 customers and experiencing losses of 13809.8 kWh / month therefore customers who make these deviations will be subject to sanctions in the form of a fine of Rp.332,830,661 for all customers who do deviation.